The Feasibility Study for Designing a Solar Power System on the Roof of a Gas Station - หงษ์ทรัพย์ภิญโญ ทยากร; สวนผกา วีระเกษตร; หงษ์สมบัติ คมสันต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the feasibility of investing in the installation of a solar photovoltaic (PV) system on the rooftop of buildings located within a gas station. Two installation scenarios were designed: Scenario 1 involves installing the PV system on the rooftop of a building located within the hazardous zone of the gas station, while Scenario 2 involves installation outside the hazardous zone. Information such as installation area, roof type, system specifications, system cost, relevant regulations, and laws concerning gas stations was collected. Once the preliminary data was obtained, each system’s energy production was simulated over a 25-year project lifespan using PVsyst software. A financial analysis was then conducted, including Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PB). The results showed that Scenario 1 used a micro-inverter system with a capacity of 60.2 kW, while Scenario 2 used a string inverter system with a capacity of 60.8 kW. The total energy produced over 25 years was 1,774,302.50 kWh and 1,835,312 kWh, respectively. The NPV values were 1,751,941.97 THB and 2,496,181.33 THB, the IRR was 16.03% and 25.72%, and the PB was 5.97 years and 3.80 years, respectively. Therefore, from an economic perspective, Scenario 2 is more attractive for investment than Scenario 1.